2018
DOI: 10.1093/asj/sjy147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retropectoral Fat Grafting in Breast Reduction by Magnetic Resonance Imaging: A Pilot Study

Abstract: Retropectoral fat grafting may contribute to maintaining the fullness of the upper pole of the breasts. This is an innovative experimental model for future studies on fat harvesting, preparation and grafting techniques, allowing the evaluation of fat graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…Few studies have provided data on fat graft retention in the retropectoral plane. One study showed that the mean fat graft retention rate in the retropectoral plane was 23.4% in the late post-operative period (24). The mean retention rate in our study was 39.28% and thus higher than their result.…”
Section: Discussioncontrasting
confidence: 62%
“…Few studies have provided data on fat graft retention in the retropectoral plane. One study showed that the mean fat graft retention rate in the retropectoral plane was 23.4% in the late post-operative period (24). The mean retention rate in our study was 39.28% and thus higher than their result.…”
Section: Discussioncontrasting
confidence: 62%